THE MAIN ISSUES OF CRIMINAL LIABILITY FOR DISCRIMINATION - Stepanyan, Zhenya (State and Law, 2024)
The Article analyzes the issues of criminal liability for discrimination, reveals the objective and subjective features of the crime, as well as highlights the gaps and shortcomings of the regulation, which may cause certain problems in practice in relation to the qualification of the crime. The research is especially relevant given the adoption of the new Criminal Code of the Republic of Armenia, which is in force since July 1, 2022. It has radicaly amended the crime of discrimination. Thus, the article analyzes in detail such mandatory features of the objective side of the crime of discrimination as the difference in treatment in a similar situation, and the circumstances justifying it.At the same time, based on the research done, it is suggested to define discrimination as a material crime, which will allow to clearly distinguish the criminal responsibility for discrimination from other types of legal responsibility.The Article is widely based on the case-law of the European Court of Human Rights regarding discrimination, as well as the recommendations, reports made and research done by international bodies. The main approaches in doctrinal sources on discrimination are also analyzed. As a result, relevant recommendations aimed at effectively overcoming existing gaps and shortcomings are made.
Keywords: Discrimination; European Court; European Convention; Difference in Treatment; Legitimate Aim; Proportionality; Discrimination by Grounds; Significant Damage